Effectiveness of "Priorix" Against Measles and Mumps Diseases in Children Born After 2004 in the United Kingdom: A Retrospective Case-control Study Using the Clinical Practice Research Datalink GOLD Database. Issue 6 (10th May 2021) - Povey, Michael; Aris, Emmanuel; Cheuvart, Brigitte; Hall, Gillian; Cohet, Catherine; Willame, Corinne
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Evidence on vaccine effectiveness (VE) may encourage vaccination and help fight the reemergence of measles and mumps in Europe. However, limited data exist on real-life effectiveness of individual measles, mumps and rubella (MMR) vaccines. This study evaluated VE of GSK's MMR vaccine ("Priorix") against measles and mumps. Methods: This retrospective, case-control study used UK data from the Clinical Practice Research Datalink GOLD linked to the Hospital Episode Statistics database to identify children 1–13 years old diagnosed with measles or mumps from January 2006 to December 2018. Cases were matched to controls according to birth month/year and practice region. Cases were identified using clinical codes (without laboratory confirmation). "Priorix" exposure was identified using vaccine batch identifiers. Children exposed to other MMR vaccines were excluded. Adjusted VE was estimated for ≥1 vaccine dose in all children, and for 1 dose and ≥2 doses in children ≥4 years at diagnosis. Results: Overall, 299 measles cases matched with 1196 controls (87.6% <4 years old), and 243 mumps cases matched with 970 controls (74.2% <4 years old) were considered. VE for ≥1 dose in all children was 78.0% (97.5% confidence interval: 67.2%–85.3%) for measles and 66.7% (48.1%–78.6%) for mumps. In children ≥4 years old, VE after 1 dose was 74.6% (–21.7% to 94.7%) for measles and 82.3% (32.7%–95.3%) for mumps, and VE after ≥2 doses was 94.4% (79.7%–98.5%) for measles and 86.5% (64.0%–94.9%) for mumps. Conclusions: "Priorix" is effective in preventing measles and mumps in real-life settings.